Pathways to sustainable transitions in a complex agricultural system: a case study of swine waste management in North Carolina - Deviney, Alison V.; Classen, John J.; Bruce, Jacklyn A. (Frontiers in Sustainable Food Systems, 2024)
North Carolina has a high density of swine farms with over 2,500 permitted commercial operations in the state and nearly half of those farms located in just two counties. Lagoon and sprayfield (LS) has been the dominant method of swine manure management for the past three decades, despite pressure to transition to environmentally superior technologies. In an LS system, animal waste is captured in pits beneath the barn floor and regularly flushed to an open inground storage area (lagoon) to undergo anaerobic treatment prior to land application as fertilizer. Although generally considered an efficient and cost-effective method of manure management, LS has negatively impacted the environment and local communities from discreet events such as lagoon breeches or flooding to ongoing issues associated with odor and disease vectors. Here we demonstrate how change may influence the North Carolina swine waste management (NC SWM) system using alternative scenarios. The scenarios are applied to a conceptual model developed using a methodology for analyzing and visualizing complex sociotechnical agricultural systems. A sociotechnical system is the integrated social and technical network related to a particular technology or practice, such as the LS regime of manure management. Many complex agriculture systems including concentrated livestock production have evolved around such regimes. Using the Multilevel Perspective Theory (MLP) as a frame for understanding the relationships between the sociotechnical regime, its surrounding landscape, and emerging niches for sustainable technology development can help align these different levels of perspective toward a common goal and support transitioning toward more sustainable practices. A farm level was added to represent the user perspective of regime technology in complex agriculture systems (MLP+F). This case study demonstrates two scenarios using the NC SWM conceptual model built on the MLP+F framework through input from a panel of diverse experts. One scenario explores whether panel recommended changes generate the desired outcome, while the other considers the systemic effect of introducing a manure dewatering process on swine operations, with and without landscape support. Both scenarios indicated a positive outcome, suggesting alignment exists across stakeholder perceptions of system behavior, although some unintended consequences could warrant further investigation.